Secure performance analysis of relay systems with multi-relay and multi-user selection - Tingjie REN; Guangqiu LI; Ying CHENG (Dianxin kexue)
The exact expressions for the non-zero secrecy capacity probability,secrecy outage probability of AF relay systems with transmit antenna selection and receive maximal ratio combining and its asymptotic secrecy outage probability at high signal to noise ratios over Rayleigh fading channel were derived respectively.The numerical results of the non-zero secrecy capacity probability and secrecy outage probability of AF relay systems with multi-relay and multi-user selection match well with their corresponding simulations,which proves the correctness of the above theoretical analysis.The analysis result of the asymptotic secrecy outage probability of AF relay systems with multi-relay and multi-user selection indicates that its secrecy diversity gain is the minimum value between the product of the number of transmit antennas at source,the number of receive antennas at the optimal relay node,and the number of relay nodes,and the product of the number of transmit antennas at the optimal relay node,the number of receive antennas at the optimal destination node,and the number of destination nodes,which is independent of the eavesdropper channel.